Analisis Kesediaan Berbagi Identitas Digital berdasarkan Faktor Self-Efficacy, Perceived Severity dan Gender - Mohammad Khaafi Radja Rihan; Diah Priharsari; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Digital identity is something that is really needed in carrying out activities on the internet, especially in social networking. Everyone who has a social network on the internet is required to provide a digital identity such as name, date of birth, telephone number and personal photo. In the current era, digital identities are often reported to be leaked, stolen, and misused by irresponsible parties. This is a problem that causes privacy concerns for social network users to share their digital identity which is personal data. In addition, privacy concerns also affect social network users in protecting their digital identity privacy. The aim of this study is to find out how social network users protect their digital identity using the Protection Motivation Theory (PMT) theory by identifying two PMT factors, namely Self-Efficacy and Perceived Severity factors to examine privacy concerns that arise on social networks. This study also aims to find out whether gender factors have differences in willingness to share digital identities on social networks. This study used the SEM-CB method by distributing questionnaires to 309 respondents. The results found that there is a positive influence on privacy concerns in the willingness to share digital identities. Another finding found that Self-Efficacy and Perceived Severity had a positive effect on privacy concerns, but not the gender factor with negative results indicating that there was no difference between genders in the willingness to share digital identity on social networks.